2006
DOI: 10.1136/jcp.2006.037606
|View full text |Cite
|
Sign up to set email alerts
|

Receptor-activated Smad localisation in Bleomycin-induced pulmonary fibrosis

Abstract: Background:Recent advances in fibrosis biology have identified transforming growth factor (TGF)-β type I receptor-mediated activation of Smads as playing a central part in the development of fibrosis. However, to date, there have been few studies that examined the localisation and distribution of receptor-activated Smads protein (R-Smads: Smad2 and 3) during the fibrosis progression.Aims:To histopathologically assess the time-course change of the localisation and distribution of the Smads protein in pulmonary … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 23 publications
4
22
0
Order By: Relevance
“…40,41 Bronchoalveolar fluid and lung tissues were collected at day 8 and day 14 when fibroblast activation in bleomycin-induced lung fibrosis model occurs. 42 Consistent with the previous observation of increased TGF-␤ in the lungs of bleomycin-stimulated Thy-1 knockout mice, we also observed increased TGF-␤ signaling in lungs from bleomycin-treated Thy-1 knockout mice. Immunohistochemical staining showed that both knockout and wild-type mice have increased nuclear accumulation of phosphorylated Smad3 in the lungs with bleomycin treatment.…”
Section: Bleomycin Treatment Increases Ltbp-4 Expression In Mouse Lunsupporting
confidence: 80%
“…40,41 Bronchoalveolar fluid and lung tissues were collected at day 8 and day 14 when fibroblast activation in bleomycin-induced lung fibrosis model occurs. 42 Consistent with the previous observation of increased TGF-␤ in the lungs of bleomycin-stimulated Thy-1 knockout mice, we also observed increased TGF-␤ signaling in lungs from bleomycin-treated Thy-1 knockout mice. Immunohistochemical staining showed that both knockout and wild-type mice have increased nuclear accumulation of phosphorylated Smad3 in the lungs with bleomycin treatment.…”
Section: Bleomycin Treatment Increases Ltbp-4 Expression In Mouse Lunsupporting
confidence: 80%
“…Our data suggest that LY2109761 attenuates profibrotic signaling directly, but also balances the complex TGFb/BMP signaling: LY2109761 dramatically reduced radiation-induced upregulation of Gremlin (Grem2) and also upregulated BMP2 expression. Moreover, LY2109761 reduced radiation-induced downstream signaling genes of TGF-b including Smads 6, 7, and 9 but also MDM2 in accordance with lung histology showing reduced p-Smad2, with increased p-Smad2 levels being associated with lung fibrosis (29). While radiation slightly increased and LY2109761 clearly decreased Smad1 phosphorylation, Smad2 or Smad3 phosphorylation was hardly affected in fibroblasts.…”
Section: Discussionmentioning
confidence: 60%
“…We isolated type II AECs from SPC.Cre.TGF␤R2 fl/fl .Rosa. Stop.lacZ mice and littermate controls at 2 wk after bleomycin administration, at which time lung TGF␤ levels are elevated (18). After AEC isolation, we performed a targeted TGF␤/ BMP-specific 96-well array (SABiosciences) to evaluate expression of TGF␤/BMP-dependent genes.…”
Section: Resultsmentioning
confidence: 99%